In-situ chemical oxidation of chlorendic acid by persulfate: Elucidation of the roles of adsorption and oxidation on chlorendic acid removal. (1st October 2019) - Taylor, Alannah; Zrinyi, Nick; Mezyk, Stephen P.; Gleason, Jamie M.; MacKinnon, Leah; Przepiora, Andrzej; Pham, Anh Le-Tuan
Abstract: The oxidation of chlorendic acid (CA), a polychlorinated recalcitrant contaminant, by heat-, mineral-, and base-activated persulfate was investigated. In pH 3–12 homogeneous (i.e., solid-free) solutions, CA was oxidized by OH and SO4 - radicals, resulting in a nearly stoichiometric production of Cl − . The rate constants for the reaction between these radicals and CA were measured at different temperatures by electron pulse radiolysis, and were found to be kOH = (8.71 ± 0.17) × 10 7 M −1 s −1 and kSO4 = (6.57 ± 0.83) × 10 7 M −1 s −1 at 24.5 °C for OH and SO4 -, respectively. CA was oxidized at much slower rates in solutions containing iron oxyhydroxide or aquifer soils, partially due to the adsorption of CA on these solids. To gain further insight into the effect of solids during in-situ remediation of CA, the adsorption of CA onto iron (hydr)oxide, manganese dioxide, silica, alumina, and aquifer soils was investigated. The fraction of CA that was adsorbed on these materials increased as the solution pH decreased. Given that the solution pH can decrease dramatically in persulfate-based remedial systems, adsorption may reduce the ability of persulfate to oxidize CA. Overall, the results of this study provide important information about how persulfate can be used to remediate CA-contaminated sites. The results also indicate that the groundwater pH and geology of the subsurface can have a significant influence on the mobility of CA. Graphical abstract: Image 1 Highlights: Activated persulfates (S2 O8 2− ) could degrade CA only under certain conditions. In homogeneous (i.e., solid-free) solutions, CA could be oxidized by . OH and SO4 - . In heterogeneous solutions, CA was removed mainly by adsorption to solids. Adsorption of CA retarded/inhibited the oxidation of CA, especially at acidic pH. CA desorption after S2 O8 2− is depleted may cause the CA concentration to rebound.